The role of fans’ responses to sponsorship activation in shaping sport sponsorship effectiveness - Junyi Bian; Benjamin Colin Cork (Journal of Applied Sports Management, 2025)
The study explored how types of benefit in sponsorship affect fans’ inference of sponsors’ motives and their consequences on sponsorship effectiveness. A total of 1,478 National Basketball Association fans were recruited via Amazon Mechanical Turk and completed surveys through Qualtrics. Findings indicated that sponsors’ motives varied with types of benefit, with egoistic motives linked to utilitarian benefit and altruistic or normative motives tied to hedonic and social benefit. These results extended previous research by exploring more than the altruistic-egoistic motive dichotomy in linking benefit types to sponsorship effectiveness, highlighting the importance of aligning benefit with fan preference to boost relevance.
Keywords: motive inference; recognizable benefits; sponsorship activation; sponsorship effectiveness